SPATIAL AND TEMPORAL ANALYSIS OF LAND USE LAND COVER CHANGES IN SARGODHA DISTRICT PUNJAB - Muhammad Sameer*; Kashif Malik; Rubina Gulzar (`, 2025)
This article discusses the change of land use and land cover (LULC) in Sargodha region of Punjab, Pakistan, for the period of 30 Years (1993-2023) using satellite imageries. The four major land cover categories that emerged were agricultural land, urban built-up land, barren land, and water bodies, using 1993, 2003, 2013, and 2023 Landsat high-resolution images. Compared to previous periods, there have been significant changes in the patterns of land use in the region. Agricultural areas which occupied an estimated 80% of the total area in the year 1993 experienced a decrease to 71% by the year 2023. This was occasioned by the rapid rate of urbanization that took place over that period. However, there was a significant change in built-up areas, during this period which rose from 5% in 1993 to 21% in 2023 indicating a significant increase in population density and built infrastructure. Barren land registered a decrease from 14% down to 7% indicating a change in land use patterns while the water bodies remained the same level at 1%. Auxiliary indicators such as the overall accuracy, user and producer accuracy, kappa coefficients, and other detailed accuracy measurements were undertaken to validate the classification. The results from the auxiliary indicators registered an overall accuracy of 93.53% in the year 2023. The results show the urgent necessity of the tools and approaches for balanced land management. The rezoning and reallocation of centrally planned activities is critical for the development of one the most important agricultural regions. Keywords: Agriculture, Built-up, Land Management, Satellite Imageries